IMPROVING STUDENTS’ UNDERSTANDING ON TEACHER’S COMMAND THROUGH TOTAL PHYSICAL RESPONSE METHOD - Anjarwati, Devi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to improve students’ understanding on teacher’s command through Total Physical Response method of the eighth grade students at SMP BP Haruniyah Pontianak academic year 2016/2017. The subject of this research was the eighth grade students of SMP BP Haruniyah Pontianak in academic year 2016/2017. In collecting the data the researcher observed the improvement of students’ understanding on teacher’s command through observation, field notes, and students’ individual test. This research was done in two cycles. The result of this research showed that Total Physical Response method can improve the eighth grade students’ understanding on teacher’s command of SMP BP Haruniyah Pontianak in academic year 2016/2017. The students were able to responds the command given by the teacher using gesture, to get involved in brainstorming activity, to listen carefully the teacher’s command, and to actively participate in performing the action. It can be concluded that students’ understanding on teacher’s command through Total Physical Response method was improved. In other words, this method can help the students in understanding the teacher’s command. Keywords: Total Physical Response Method, Students’ Understanding, Teacher’s Command, Classroom Action Research